Pola Perilaku Guru Dalam Meningkatkan Pendidikan Karakter Siswa di SMAN 8 MEDAN - Hidayati, Syari; Rahmi, Wardatur; Yasri, Ahmad (IKAMAS: Manajemen Pendidikan Islam, 2022)
This study aims to find out about the behavior patterns and strategies used by SMAN 8 teachers in improving character education for students, considering that today the character of the nation's children is increasingly immoral. The type of research used in this research is descriptive qualitative. The research approach used is qualitative research, with descriptive methods. In this case, the description will be more to provide a review in the form of a real and comprehensive picture related to the implementation of online learning. This study uses observation, interviews and documentation techniques in the data collection process. From the results of the study, it is clear that the behavior patterns and strategies used by SMAN 8 teachers to improve character education in students are very good and have been successfully implemented and imitated by their students.